Развивающее образование: от теории к практике - Дусавицкий, А.К. (My University, 2011)
Анотація У статті розглянуто психологічні основи системи розвивального навчання (РН) та історія її створення. Показана ведуча роль факультету психології Харківського науціонального університету імені В.Н.Каразіна в психолого-педагогічних дослідженнях розвитку особистості в систмі РН в Україні. Ключові слова: культурно-історична теорія, навчання, розвиток, розвивальне навчання. Annotation Developing Education: From Theory to Practice The present paper deals with the question of psychological bases system of developing education and the history of it creation. The work shows the leading role of psychology faculty of Kharkov national university named after V.N. Karazin in psychological and pedagogical developing research of personality in the system of developing education in Ukraine. Keywords: cultural-historical theory, training, development, developing training.
Keywords: культурно-історична теорія; навчання; розвиток; розвивальне навчання